TIER2: enhancing Trust, Integrity and Efficiency in Research through next-level Reproducibility - Tony Ross-Hellauer; Thomas Klebel; Alexandra Bannach-Brown; Serge P.J.M. Horbach; Hajira Jabeen; Natalia Manola; Teodor Metodiev; Haris Papageorgiou; Martin Reczko; Susanna-Assunta Sansone; Jesper Schneider; Joeri Tijdink; et al. (Research Ideas and Outcomes, 2022)
Lack of reproducibility of research results has become a major theme in recent years. As we emerge from the COVID-19 pandemic, economic pressures and exposed consequences of lack of societal trust in science make addressing reproducibility of urgent importance. TIER2 is a new international project funded by the European Commission under their Horizon Europe programme. Covering three broad research areas (social, life and computer sciences) and two cross-disciplinary stakeholder groups (research publishers and funders) to systematically investigate reproducibility across contexts, TIER2 will significantly boost knowledge on reproducibility, create tools, engage communities, implement interventions and policy across different contexts to increase re-use and overall quality of research results in the European Research Area and global R&I, and consequently increase trust, integrity and efficiency in research.